IMPLIKASI INTEGRASI DAN MERGER PADA DOMINASI PASAR META PLATFORM DAN WALT DISNEY - Akhsan Fadlurrahman; Ayu Nursasi; Nahdiyah Ulul Azmi; Naerul Edwin Kiky Aprianto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
In the era of digitalization, many new companies have emerged with their own advantages. However, if they are unable to compete, they tend to survive for a short time. One way to survive is through integration and merger. This research uses a descriptive qualitative method with a literature study. The results show that Meta Platform and Walt Disney dominate the market in their respective sectors, thus falling into the oligopoly market category. Meta dominates social networks by integrating WhatsApp and Instagram, copying the Reels feature to compete with TikTok, and connecting platforms to improve efficiency and user convenience. This strategy strengthened its position with billions of monthly active users. Walt Disney expanded its influence through mergers with Pixar, Marvel, 21st Century Fox and Lucasfilm, and expanded into theme parks, consumer products and digital services such as Disney+. These moves saw Disney dominate the global box office and earn huge revenues.